Professionalism Through Role Clarity: Analysis of Bellboy Job Description Implementation at the Alana Hotel & Convention Center Solo - Muhtar Risky Ega Virdaus; Prasiwi Citra Resmi; Suci Purwandari (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the implementation of the bellboy job description at The Alana Hotel & Convention Center Solo and its relationship to guest satisfaction. The research employs a qualitative descriptive approach to obtain a comprehensive understanding of how the job description is applied in both administrative and operational aspects. Data were collected through observation, interviews with bellboys and a front office supervisor, and documentation analysis. The findings show that the bellboys’ job description consists of two main dimensions: administrative duties, including vehicle and luggage records, and operational duties, such as guest assistance and lobby maintenance. In general, bellboys have demonstrated professional attitudes and responsiveness in providing services; however, inconsistencies still occur during peak hours due to limited staff and less effective coordination between departments. The study concludes that a clear and consistently implemented job description has a positive impact on service quality and guest satisfaction. It is recommended that hotel management conduct periodic evaluations and provide continuous training to improve coordination, time management, and communication skills among bellboys.